The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Ye.V. Bystrovskaya – Postcholecystectomy syndrome: clinical variants, prediction and prophylaxis.N.I. Zhernakova – Clinical neuroimmunoendocrinology of peptic ulcer in elderly patients. K.T. Umbetova – Autoimmune signs in patients with viral hepatites.A.A. Nizhevich – Clinical and morphological characteristic, genetic markers, diagnostics and treatment Helicobacter pylori-associated gastroduodenal diseases in children.